The Polycomb group gene rnf2 is essential for central and enteric neural system development in zebrafish - Feng, Gang; Sun, Yuhua (Frontiers in Neuroscience, 2022)
The development of central nervous system (CNS) and enteric nervous system (ENS) is under precise and strict control in vertebrates. Whether and how the Polycomb repressive complex 1 (PRC1) is involved in it remain unclear. To investigate the role of PRC1 in the nervous system development, using CRISPR/Cas9 technology, we have generated mutant zebrafish lines for the rnf2 gene which encodes Ring1b, the enzymatic component of the PRC1 complex. We show that rnf2 loss of function leads to abnormal migration and differentiation of neural crest and neural precursor cells. rnf2 mutant embryos exhibit aganglionosis, in which the hindgut is devoid of neurons. In particular, the formation of 5-HT serotonin neurons and myelinating glial cells is defective. Furthermore, ectopic expression of ENS marker genes is observed in forebrain of rnf2 mutant embryos. These findings suggest that the rnf2 gene plays an important role in the migration and differentiation of neural precursor cells, and its absence leads to abnormal development of ENS and CNS in zebrafish.